Question
upstudy study bank question image url

Question 5 Express \( \frac{25}{(x-2)(x+3)^{2}} \) in the form \( \frac{A}{x-2}+\frac{B}{x+3}+\frac{C}{(x+3)^{2}} \) and hence find \( \int \frac{25}{(x-2)(x+3)^{2}} d x \)

Ask by Perkins Craig. in the United Kingdom
Feb 23,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The integral of \( \frac{25}{(x-2)(x+3)^2} \) with respect to x is \( \ln\left|\frac{x-2}{x+3}\right| + \frac{5}{x+3} + C \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

Bonus Knowledge

To express \( \frac{25}{(x-2)(x+3)^{2}} \) in the form \( \frac{A}{x-2}+\frac{B}{x+3}+\frac{C}{(x+3)^{2}} \), we start by setting up the equation: \[ \frac{25}{(x-2)(x+3)^{2}} = \frac{A}{x-2} + \frac{B}{x+3} + \frac{C}{(x+3)^{2}}. \] To combine the right side, we find a common denominator, which is \((x-2)(x+3)^{2}\): \[ \frac{A(x+3)^{2} + B(x-2)(x+3) + C(x-2)}{(x-2)(x+3)^{2}}. \] Now, we have: \[ 25 = A(x+3)^{2} + B(x-2)(x+3) + C(x-2). \] Next, we want to determine \(A\), \(B\), and \(C\). We can use convenient values of \(x\) to solve for these coefficients. 1. Set \(x = 2\): \[ 25 = A(2+3)^{2} \implies 25 = A(5)^{2} \implies 25 = 25A \implies A = 1. \] 2. Set \(x = -3\): \[ 25 = B(-3-2)(-3+3) + C(-3-2) \implies 25 = -5C \implies C = -5. \] 3. To find \(B\), substitute \(A\) and \(C\) back into the original equation. Let's use \(x = 0\): \[ 25 = 1(0+3)^{2} + B(0-2)(0+3) - 5(0-2). \] This gives: \[ 25 = 1(9) + B(-2)(3) + 10 \implies 25 = 9 - 6B + 10 \implies 25 = 19 - 6B \implies 6B = -6 \implies B = -1. \] Now we have: \[ A = 1, \quad B = -1, \quad C = -5. \] Thus, we can express \( \frac{25}{(x-2)(x+3)^{2}} \) as: \[ \frac{1}{x-2} - \frac{1}{x+3} - \frac{5}{(x+3)^{2}}. \] Next, we integrate: \[ \int \frac{25}{(x-2)(x+3)^{2}} \, dx = \int \left( \frac{1}{x-2} - \frac{1}{x+3} - \frac{5}{(x+3)^{2}} \right) \, dx. \] This results in: \[ \int \frac{1}{x-2} \, dx - \int \frac{1}{x+3} \, dx - 5 \int \frac{1}{(x+3)^{2}} \, dx. \] Calculating each part: 1. \( \int \frac{1}{x-2} \, dx = \ln |x-2| + C_1 \), 2. \( \int \frac{1}{x+3} \, dx = \ln |x+3| + C_2 \), 3. \( \int \frac{1}{(x+3)^{2}} \, dx = -\frac{1}{x+3} + C_3 \). Putting it all together, the final result of the integral is: \[ \ln |x-2| - \ln |x+3| + \frac{5}{x+3} + C. \] Thus, the integral of \( \frac{25}{(x-2)(x+3)^2} \) is: \[ \ln \left| \frac{x-2}{x+3} \right| + \frac{5}{x+3} + C. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy